2017
DOI: 10.1111/jar.12358
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge and attitudes about end of life: Evaluation of three instruments designed for adults with intellectual disability

Abstract: People with ID can reliably complete assessments about end-of-life. Generally, each instrument was found to be comprehensible, reliable and valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Nevertheless, the experiences of people with intellectual disability are at the heart of our concerns. Of the twelve papers reporting original data, only three (Irwin et al., ; McKenzie, Mirfin‐Veitch, Conder, & Brandford, ; Stancliffe, Wiese, Read, Jeltes, & Clayton, ) had people with intellectual disability as research participants. In their review of end‐of‐life decision making, Kirkendall, Linton, and Farris () commented on the lack of research involving participants with intellectual disability.…”
Section: Whose Voices Are Represented?mentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, the experiences of people with intellectual disability are at the heart of our concerns. Of the twelve papers reporting original data, only three (Irwin et al., ; McKenzie, Mirfin‐Veitch, Conder, & Brandford, ; Stancliffe, Wiese, Read, Jeltes, & Clayton, ) had people with intellectual disability as research participants. In their review of end‐of‐life decision making, Kirkendall, Linton, and Farris () commented on the lack of research involving participants with intellectual disability.…”
Section: Whose Voices Are Represented?mentioning
confidence: 99%
“…Stancliffe et al. () reported no adverse events and concluded that participants had been able to make appropriate, self‐determined decisions to discontinue participation. They argued that this approach was more respectful than the paternalistic protection of excluding people from research participation.…”
Section: Whose Voices Are Represented?mentioning
confidence: 99%
See 3 more Smart Citations